At leve gennem tal: Brugen af måleapparater i håndteringen af livsstilssygdomme i Danmark - Oxlund, Bjarne (Tidsskrift for Forskning i Sygdom og Samfund, 2012)
The advent of preventive health and medicine has led to a situation, where the risks of life style diseases are being medicated and where health understood as physical exercise and healthy diet have become a moral imperative. Many elderly Danes thus seek to manage their health condition by measuring their own bodies as well as activities of daily living through the use of devices such as weighing scales, blood pressure meters, pedometers, and bicycle computers. The results of these measurements are then matched against the scores that epidemiological surveys have established as the normal states. But what sense do people make of these measurement practices? And which bodily perception is promoted by the use of numbers? Based on preliminary insights from an ongoing fieldwork in Vordingborg municipality, this article analyzes two stories of elderly women for whom measurement of activities and bodily conditions has become a pivotal point in their everyday lives.